2019
DOI: 10.4236/jwarp.2019.1112085
|View full text |Cite
|
Sign up to set email alerts
|

Use of Numerical Groundwater Modeling to Assess the Feasibility of Aquifer Storage and Recovery (ASR) in the Wadi Watir Delta, Sinai, Egypt

Abstract: The lack of water resources in Egypt's Sinai Peninsula is a major constraint for further socioeconomic development, and flash floods in this region can damage roads and infrastructure. The Wadi Watir basin is the main water source for the groundwater aquifer, which supplies fresh water to Nuweiba city, where demands for groundwater are increasing. The objective of this research was to assess the hydrogeological suitability of installing Aquifer Storage and Recovery (ASR) systems in the Wadi Watir delta by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The suitability map has been compared with the previous study conducted by Sallam [6], who studied the feasibility of installing ASR in the study area. The comparison shows that the highly potential MAR site locations on the suitability map are near to the suggested ASR site locations "A1", "A2" and "A3" proposed by Sallam [6] (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The suitability map has been compared with the previous study conducted by Sallam [6], who studied the feasibility of installing ASR in the study area. The comparison shows that the highly potential MAR site locations on the suitability map are near to the suggested ASR site locations "A1", "A2" and "A3" proposed by Sallam [6] (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…The suitability map has been compared with the previous study conducted by Sallam [6], who studied the feasibility of installing ASR in the study area. The comparison shows that the highly potential MAR site locations on the suitability map are near to the suggested ASR site locations "A1", "A2" and "A3" proposed by Sallam [6] (Figure 6). Sallam [6] concluded that the "A1", "A2" and "A3" site locations are characterized by a high recovery efficiency at low dispersivity compared to the latter, especially "A1", using the numerical modeling method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations